Professional ethics in construction and surveying - Watts, Greg (Gregory N.); Challender, Jason; Higham, Anthony; McDermott, Peter (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This textbook responds to the increasing demand for practical, industry aligned, ethical practices in quantity surveying, construction management and related AEC professions"--
OCLC-licensed vendor bibliographic record.
Keywords: Construction workers -- Professional ethics; Building -- Professional ethics; Quantity surveyors -- Professional ethics; Quantity surveying -- Professional ethics; Construction industry -- Moral and ethical aspects -- Great Britain